M MODEL PENGAJARAN LANGSUNG UNTUK PENINGKATAN HASIL BELAJAR TEMATIK TERPADU DI SEKOLAH DASAR - Nofia Henita; Darmansyah (Study program PGSD FKIP Universitas Bung Hatta, 2023)
Describes the improvement of students' integrated thematic learning outcomes using a direct teaching model. Data collection techniques use test techniques in the form of learning outcomes tests and non-test techniques in the form of observation of teacher activities and student activities. This research is a class action research using the Kemmis and Mc Taggart models. The study was conducted in two cycles. Sabjek is a grade 1 student of State Elementary School 12 Pahambek which numbers 20 people. Teacher activity at the first meeting was 78% and in cycle II it was 92% . Therefore, the use of direct teaching models can improve the integrated thematic teaching and learning process in elementary schools.